Influence of intramolecular hydrogen bonds on the binding potential of methylated β-cyclodextrin derivatives - Wenz, Gerhard (Beilstein Journal of Organic Chemistry, 2012)
Various heptasubstituted derivatives of β-cyclodextrin (β-CD) bearing 1, 2 and 3 methyl substituents per glucose unit were synthesized by regioselective methods. Binding free energies and binding enthalpies of these hosts towards 4-tert-butylbenzoate and adamantane-1-carboxylate were determined by isothermal titration microcalorimetry (ITC). It was found that methyl substituents at the secondary positions of β-CD lead to a tremendous reduction of the binding potential, while methylation at the primary positions significantly improved binding. Stabilizing intramolecular hydrogen bonds between the glucose units were made responsible for the high binding potentials of those β-CD derivatives that possess secondary hydroxy groups.
Keywords: binding constant; cyclodextrin; hydrogen bond; methylation; regioselective